Identifikasi Kesehatan Sungai Menggunakan Pemantauan Biologis Makroinvertebrata Di Sungai Pusur, Provinsi Jawa Tengah, Indonesia : River Health Identification using macroinvertebrate biological monitoring in the Pusur River, Central Java Province, Indonesia. - Nugraha, Nanda Satya; Putra, Dian Pratama; Bimantio, Mohammad Prasanto; Ferhat, Amallia; Zakaria, Rama (HUTAN TROPIKA, 2023)
Biological assessment is an option in determining river quality, in this case related to river health. The biological assessment indicators used aquatic macroinvertebrates with research sites in the Pusur River which are located in Boyolali and Klaten Regencies, Central Java Province, Indonesia. The use of macroinvetebrata as an indicator because they are very sensitive to changes in water quality, one of which is the EPT group (Ephemeroptera, Plecoptera, and Trichoptera). Sources of river pollution will affect the existence of EPT and there are macroinvertebrates that are adaptive to contamination. This study was conducted at three monitoring stations located in the Pusur River, namely in the upstream, middle and downstream sections where each station had 6 repetitions in sampling followed by calculating the macroinvertebrate assessment index value. The results of the study show that the upstream station has an index value of 2.11 which means it is moderately polluted, the middle station has an index value of 2.40 which means it is moderately polluted and the downstream station has a value of 2.35 which means it is moderately polluted. From these results it is indicated that contamination into the river has started from the upstream area where the contamination originates from the disposal of unprocessed cow manure into river bodies, while in the middle and downstream areas the contamination that occurs is caused by dumping garbage, household waste and the use of pesticides and chemical fertilizers in agricultural ecosystem.